2003
DOI: 10.1074/jbc.m207637200
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Leukemia Cells Is Accompanied by Alterations in the Levels and Localization of Nucleolin

Abstract: Molecular defects in apoptotic pathways are thought to often contribute to the abnormal expansion of malignant cells and their resistance to chemotherapy. Therefore, a comprehensive knowledge of the mechanisms controlling induction of apoptosis and subsequent cellular disintegration could result in improved methods for prognosis and treatment of cancer. In this study, we have examined apoptosis-induced alterations in two proteins, nucleolin and poly(ADP-ribose) polymerase-1 (PARP-1), in U937 leukemia cells. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 78 publications
(72 reference statements)
5
81
0
2
Order By: Relevance
“…It is possible that other anticancer drugs which inhibit cell proliferation or promote cellular differentiation may also induce apoptosis via nucleolin down-regulation. For example, induction of apoptosis in U937 leukemia cells is accompanied by notable decreases in the levels of nuclear and cytoplasmic nucleolin (55). Under these conditions less nucleolin would be available in the cytoplasm to stabilize bcl-2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that other anticancer drugs which inhibit cell proliferation or promote cellular differentiation may also induce apoptosis via nucleolin down-regulation. For example, induction of apoptosis in U937 leukemia cells is accompanied by notable decreases in the levels of nuclear and cytoplasmic nucleolin (55). Under these conditions less nucleolin would be available in the cytoplasm to stabilize bcl-2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some autoantigens, such as ribosomal RNPs, previously described to resist proteolysis (Wu et al, 2001) have recently been shown to be cleaved and expressed at the cell surface: six proteins (S15, P0, L5, L6, L36a, L41) have been found to follow this pathway (Nishida et al, 2002). Nucleolin is one of the most studied protein in the nucleolus and it has recently been reported (Mi et al, 2003) to decrease in UV-induced apoptosis, in parallel with PARP-1 degradation.Interestingly, nucleolin and several other nuclear protein accumulate within blebs which are extruded at the cell sur- …”
mentioning
confidence: 99%
“…Evidence suggests that it may also have a role as an accessory protein in miRNA biogenesis. Nucleolin is predominantly a nucleolus-localized protein; however, in a number of different cancers, nucleolin is found largely in the cytoplasm (21)(22)(23)(24). In the cytoplasm, nucleolin functions to stabilize the mRNA of bcl-2, thereby inhibiting apoptosis (21).…”
mentioning
confidence: 99%